Reconstructing the Theological Foundation of Professional Zakat: A Semantic-Ushuli Reading of the Hadith of Mu’az ibn Jabal: Rekonstruksi Landasan Teologis Zakat Profesi: Pembacaan Semantik-Ushuli terhadap Hadis Mu'az bin Jabal - Farhan Septyansah Farhan; Muhammad Ghifari Ghifari; Jaka Gyanovan (Institut Agama Islam Negeri Kerinci, 2026)
This study aims to reconstruct the theological basis of professional zakat through a semantic-ushuli analysis of the hadith concerning the Prophet's dispatch of Mu’az ibn Jabal to Yemen as narrated in Sahih al-Bukhari. Contemporary discussions of professional zakat have predominantly focused on jurisprudential issues, particularly the determination of nisab and hawl, while the theological foundation of its legal obligation embedded in the primary hadith sources has received limited scholarly attention. Employing a qualitative normative approach based on library research, the study integrates three analytical stages: linguistic-semantic analysis of the hadith text, interpretation through the framework of Maqasid al-Shari’ah, and qiyas as a supporting juridical mechanism. The analysis demonstrates that the phrase fi amwalihim constitutes a lafz ʿamm (general expression) encompassing all forms of productive wealth, whereas the phrase min aghniyaihim establishes financial capability rather than the type of asset as the principal criterion for zakat liability. Consequently, contemporary professional income fulfils the characteristics of al-mal al-nami (productive wealth) and ghinaʾ (financial sufficiency), thereby falling within the scope of the Prophetic text. The study further argues that professional zakat should not be regarded as an independent legal innovation but as a theological implication inherent in the universal wording of the hadith. These findings provide a stronger theological and methodological foundation for the contemporary legitimacy of professional zakat and reinforce its role in realizing the distributive objectives of Islamic law.